Efficacy and adverse effects of drugs used to treat adult cystic fibrosis. (March 2015) - Chopra, Ravi; Paul, Lisa; Manickam, Rajapriya; Aronow, Wilbert S; Maguire, George P
<x xml:space="preserve">Abstract</x> Introduction: Cystic fibrosis (CF) is an autosomal recessive disease and is the most commonly seen monogenetic disease in Caucasians. The disease has various manifestations resulting from the abnormal thick secretions, most common being chronic lung infection and airway obstruction. Many new promising drugs have appeared on the horizon over the years. This review here is an attempt to bring together the various treatments being used to prolong and enhance the quality of life of CF patients. Areas covered: A literature review of published as well as ongoing clinical trials, meta-analysis and systematic reviews regarding the drugs used in CF management was carried out using PubMed and Ovid databases. Expert opinion: New concepts have been formed and some positive results in this direction have already led to the approval of cystic fibrosis transmembrane conductance regulator potentiator drug. Gene therapy and stem cell therapy are under development. The current therapies such as dornase alfa and pancreatic enzymes targeting the symptoms continue to evolve as they play an important complementary role. Development of new simple and cost-effective markers, which help assess the efficacy and safety of these constantly emerging new drugs, is also being investigated.